2020
DOI: 10.1177/0093854820977581
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Personal and Perceived Organizational Characteristics Associated With Juvenile Probation Staff Job Satisfaction

Abstract: Satisfied employees are essential to an organization, as they are often the primary means for meeting organizational needs. Job satisfaction is particularly important among criminal justice agencies, specifically probation agencies that largely rely on personnel for the supervision and rehabilitation of individuals. Yet, the correlates of job satisfaction among juvenile probation staff are largely unknown. Following organizational climate theory, the current study utilizes baseline data from the Juvenile Justi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 63 publications
1
7
0
Order By: Relevance
“…This study focused on the Staff Competency driver, because probation officers have direct contact with justice-involved persons, and thus, implementation science would suggest that the Staff Competency driver is achieved by: (a) providing initial training on EBPs, (b) selecting officers who are open to using EBPs, receiving constructive feedback on their use of EBPs, and incorporating the feedback into their supervision sessions with clients, and (c) the use of coaching to provide opportunities for individualized follow-up support after the initial training (e.g., Alexander, 2011; Waters et al, 2013). However, based on the strong relationship between job dissatisfaction and negative perceptions regarding EBPs found in this study and found in prior research (e.g., Krupa, 2021; Rhineberger-Dunn & Mack, 2020), after training officers and requesting that they use EBPs, it may be important to allocate resources to increase (or maintain) job satisfaction, rather than expending the majority of resources focusing on the officers’ adherence to using the EBPs (e.g., increasing skill proficiency).…”
Section: Discussionsupporting
confidence: 49%
See 4 more Smart Citations
“…This study focused on the Staff Competency driver, because probation officers have direct contact with justice-involved persons, and thus, implementation science would suggest that the Staff Competency driver is achieved by: (a) providing initial training on EBPs, (b) selecting officers who are open to using EBPs, receiving constructive feedback on their use of EBPs, and incorporating the feedback into their supervision sessions with clients, and (c) the use of coaching to provide opportunities for individualized follow-up support after the initial training (e.g., Alexander, 2011; Waters et al, 2013). However, based on the strong relationship between job dissatisfaction and negative perceptions regarding EBPs found in this study and found in prior research (e.g., Krupa, 2021; Rhineberger-Dunn & Mack, 2020), after training officers and requesting that they use EBPs, it may be important to allocate resources to increase (or maintain) job satisfaction, rather than expending the majority of resources focusing on the officers’ adherence to using the EBPs (e.g., increasing skill proficiency).…”
Section: Discussionsupporting
confidence: 49%
“…Moreover, input in decision-making and safety trainings were related to job satisfaction, but not significantly related to job stress (Rhineberger-Dunn & Mack, 2020). Furthermore, Krupa (2021) examined the associations between personal and organizational characteristics and job satisfaction and found that organizational characteristics, such as communication, supervisory support, and organizational support, were associated with increased job satisfaction while personal characteristics, such as caseload size, experience, and tenure, were not significantly related to job satisfaction. Thus, the agency’s approach to ameliorating job satisfaction may need to focus more on staff retention.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations